Functional connectivity reveals dissociable ventrolateral prefrontal mechanisms for the control of multilingual word retrieval. Issue 1 (13th September 2019) - Branzi, Francesca M.; Martin, Clara D.; Carreiras, Manuel; Paz‐Alonso, Pedro M.
Abstract: This functional magnetic resonance imaging study established that different portions of the ventrolateral prefrontal cortex (vlPFC) support reactive and proactive language control processes during multilingual word retrieval. The study also examined whether proactive language control consists in the suppression of the nontarget lexicon. Healthy multilingual volunteers participated in a task that required them to name pictures alternately in their dominant and less‐dominant languages. Two crucial variables were manipulated: the cue‐target interval (CTI) to either engage (long CTI) or prevent (short CTI) proactive control processes, and the cognate status of the to‐be‐named pictures (noncognates vs. cognates) to capture selective pre‐activation of the target language. The results of the functional connectivity analysis showed a clear segregation between functional networks related to mid‐vlPFC and anterior vlPFC during multilingual language production. Furthermore, the results revealed that multilinguals engage in proactive control to prepare the target language. This proactive modulation, enacted by anterior vlPFC, is achieved by boosting the activation of lexical representations in the target language. Finally, control processes supported by both mid‐vlPFC and the left inferior parietal lobe, were similarly engaged by reactive and proactive control, possibly exerted on phonological representations to reduce cross‐language interference.